REDEFINING INTERPRETERS’ AND TRANSLATORS’ ROLES: UNVEILING FORENSIC EXPERTISE IN LAWFUL INTERCEPTION OF COMMUNICATION - Hohl Zuercher, Franziska; Capus, Nadja (REI - REVISTA ESTUDOS INSTITUCIONAIS, 2024)
In multilingual societies, translation and interpreting play pivotal roles in facilitating access to essential services provided by public institutions for individuals speaking languages other than the official language. However, prevailing assumptions among professionals in these institutions often regard translation as a mechanical process, overlooking the inherent interpretive nature of interlingual transfer. This study examines the interventions of intercept interpreters/translators (IITs) in the translation process within the criminal justice system, focusing on covert communication surveillance. An analysis of 538 translated intercept records (TIRs) reveals that IITs significantly intervene in selecting and interpreting content, often decrypting vague or encoded terms used in intercepted conversations. These interventions, which include annotations and comments, shape the evidentiary value and comprehensibility of TIRs. The findings highlight the complex nature of communication surveillance and underscore the need to reconsider the roles of translators and interpreters. This study contributes to our overall understanding about the ambiguous roles interpreters and translators may play in public institutions. As for IITs, the study suggests a re-evaluation of their roles that recognizes their specialized skills and multiple tasks.